Modification of the existing maximum residue levels for acibenzolar‐S‐methyl in beans with pods and peas with pods. (26th February 2021) - ,; Anastassiadou, Maria; Bernasconi, Giovanni; Brancato, Alba; Carrasco Cabrera, Luis; Ferreira, Lucien; Greco, Luna; Jarrah, Samira; Kazocina, Aija; Leuschner, Renata; Magrans, Jose Oriol; Miron, Ileana; et al.
Abstract: In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant Syngenta France SAS submitted a request to the competent national authority in France to amend the residue definition for risk assessment and to modify the existing maximum residue levels (MRLs) for the active substance acibenzolar‐S‐methyl in beans (with pods) and peas (with pods). The toxicological data submitted in support of this MRL application were found to be sufficient to conclude that the plant metabolite 4‐OH acibenzolar acid is not genotoxic in vitro, however lacking investigation of the general toxicity, a definitive conclusion cannot be derived whether 4‐OH acibenzolar acid (free and conjugated) should be included or excluded from the residue definition for risk assessment for all commodities belonging to the groups of leafy crops and pulses/oilseeds. The data submitted in support of the request were found to be sufficient to derive MRL proposals on the basis of the current residue definition (sum of acibenzolar‐S‐methyl and acibenzolar acid (free and conjugated), expressed as acibenzolar‐S‐methyl) for the intended uses on lettuces and salad plants, beans (with pods) and peas (with pods). The available residue trials are sufficient to derive MRL proposals of 1 mg/kg for beans with pods and peas with pods. The submitted information did not provide evidence that the existing MRL has to be changed for the intended uses on lettuces and other salad plants. For herbs and edible flowers, data gaps were identified which precluded the derivation of MRL proposals. The consumer risk assessment for the current residue definition did not identify an unacceptable risk for consumers. The indicative exposure calculations performed for the metabolite 4‐OH acibenzolar indicate that exposure to this metabolite is lower than the exposure to acibenzolar‐S‐methyl and acibenzolar acid (free and conjugated). However, considering the data gaps identified, a definitive conclusion cannot be derived by EFSA on the risk for consumers related to the intake of residues of 4‐OH acibenzolar acid. The reliable end points appropriate for use in regulatory risk assessment are presented.